First record of the ant genus Myrcidris (Formicidae: Pseudomyrmecinae) from Colombia - GUERRERO, ROBERTO J. (Revista Colombiana de Entomología, 2009)
The genus Myrcidris and its only described species, M. epicharis are registered for the first time from Colombia. The possible distribution throughout the Amazon watershed of the genus Myrcidris and its obligate relation with ant- plant Myrcia are discussed.